Anogenital distance and reproductive outcomes in 9‐ to 11‐year‐old boys: the INMA‐Granada cohort study. (16th August 2018) - Freire, C.; Ocón‐Hernández, O.; Dávila‐Arias, C.; Pérez‐Lobato, R.; Calvente, I.; Ramos, R.; Olea, N.; Fernández, M. F.
Abstract: Background: Studies examining the association of anogenital distance (AGD), a biomarker of prenatal androgen exposure, with sexual development in children are lacking. Objective: To assess the association between AGD measures and reproductive outcomes, including puberty onset, testicular volume, reproductive hormone levels, and urogenital malformations in boys aged 9–11 years. Materials and methods: A cross‐sectional study was conducted among children belonging to the Spanish Environment and Childhood (INMA) Project, a population‐based birth cohort study. The present sample included 279 boys for whom data were available on AGD, pubertal stage, testicular volume, and relevant covariates. Out of the boys with AGD data, 187 provided a blood sample for hormone analysis. AGD was measured from the center of the anus to the base of the scrotum. Pubertal development was assessed according to Tanner stage of genital development (G1–G5), and testicular volume was measured with an orchidometer. Results: After adjusting for potential confounders, logistic regression analysis showed that AGD was positively associated with testicular volume but not with Tanner stage (>G1 vs. G1), serum hormone levels, or undescended testis. Regardless of their age, body mass index, and Tanner stage (G1 or >G1), boys with longer AGD showed increased odds of a testicular volume >3 mL (OR = 1.06, 95%CI = 1.00–1.19 per 10% increment in AGD; and OR = 3.14, 95%CI = 0.99–9.94 for AGD >42 mm vs. <33 mm). Discussion: Longer AGD was associated with testicular growth, an indicator of gonadarche, but not with other reproductive outcomes. Conclusions: Although AGD was positively associated with testicular volume, it remains unclear whether AGD predicts testis size at puberty or is related to puberty onset.